Vibrational spectroscopic and Hirshfeld surface analysis of N,N'-(azanediylbis(2,1-phenylene))bis(2-chloropropanamide) - Polat, Aysegul Suzan; Gumus, Ilkay; Arslan, Hakan (European Journal of Chemistry, 2019)
The title molecule, N,N'-(azanediylbis(2,1-phenylene))bis(2-chloropropanamide) (LNNN) was synthesized and characterized by means of Hirshfeld surface analysis and vibrational (FT-IR and RAMAN) studies. Ab-initio Hartree-Fock (HF) and density functional theory (DFT; BLYP, B3LYP, B3PW91 and mPW1PW91) calculations were accomplished using 6-31G(d,p) and 6-311G(d,p) basis sets. The comparison of calculated bond lengths and angles with X-ray crystal structure shows sufficient agreement. The solid phase FT-IR and FT-RAMAN spectra of LNNN have been recorded in the regions 4000-525 cm-1 and 4000-50 cm-1, respectively. A comparative analysis between the calculated and experimental vibrational frequencies was carried out and significant bands were assigned. The results indicated a good correlation between experimental and theoretical IR and RAMAN frequencies. A detailed analysis of the intermolecular interactions via Hirshfeld surface analysis and fingerprint plots revealed that supramolecular structure of the LNNN is stabilized mainly by the formation of H···H, C···H, Cl···H ve O···H intermolecular interactions.